PEMBUATAN SISTEM AKADEMIK PADA SMA PGII DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - An Nisa Sari Khoiriah; Radiant V. Imbar (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Senior high school of Persatuan Guru Islam Indonesia (senior high school of PGII) is one of the international schools located in the city of Bandung , West Java . PGII high school wants to develop an academic system .The academic system will be utilized by students and teacher to create the report of students values at the school. The main feature of this application is the recommendation for the student to represent a school. This recommendation was made using the Simple Additive Weighting (SAW) Method. SAW method is one Decision Support System (DSS) methods that uses a weighted sum of each alternative at every attributes.Keywords: academic system, SAW, senior high school.